2018
DOI: 10.3390/en12010086
|View full text |Cite
|
Sign up to set email alerts
|

Superconducting AC Homopolar Machines for High-Speed Applications

Abstract: This paper presents a novel high-speed alternating current (AC) homopolar motor/generator design using stationary ReBCO excitation windings. Compact, lightweight, high-efficiency motors and generators are sought for a multitude of applications. AC homopolar synchronous machines are an ideal choice for such applications as these machines enable very high rotational frequencies. These machines include both AC armature winding and direct current (DC) excitation winding within the stationary part of the machine. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 17 publications
0
26
0
Order By: Relevance
“…Four different material law models have been systematically compared in [44], including (7) and (10). It is concluded that when at a low transport current (below 0.4 Ic0), the magnetization losses obtained by (7) and (10) are almost the same. In fact, (7) is in essence a simplified version of (10) with specific parameters.…”
Section: Magneto-angular Anisotropymentioning
confidence: 99%
“…Four different material law models have been systematically compared in [44], including (7) and (10). It is concluded that when at a low transport current (below 0.4 Ic0), the magnetization losses obtained by (7) and (10) are almost the same. In fact, (7) is in essence a simplified version of (10) with specific parameters.…”
Section: Magneto-angular Anisotropymentioning
confidence: 99%
“…The output power of an electrical machine is proportional to both rotational frequency and rotor excitation field [1]. The friction and heat generated by conventional bearings limit the design speed of any electrical machine.…”
Section: Introductionmentioning
confidence: 99%
“…Synchronous homopolar machines have been known for a long time and are used in various equipment such as generators in aircrafts and trains [12], welding inverters [13], and flywheel energy storage systems [14]. Moreover, in [4,5,11,15,16], SHMs were presented as traction motors.…”
Section: Introductionmentioning
confidence: 99%